Determination of Perspective Directions for The Foreign Economic Activity Development in Large Russian Industrial Regions (On the Example of The Chelyabinsk Region) - Irina Y. OKOLNISHNIKOVA1; Antonina I. UKHOVA2; Alexey D. OKOLNISHNIKOV2; Mark S. ANASTASOV3 (Communications of International Proceedings, 2020)
The article is devoted to the study of the ways of development of foreign economic activity of large Russian industrial regions. The authors substantiated the key guidelines for the diversification of national exports and showed that its successful development is based on the interaction of the federal center and regions. On the example of a large industrial region - the Chelyabinsk region, promising geographical directions for the development of regional exports are identified and ways of developing each of the directions are proposed. The authors have proposed branches of the regional economy that are promising in terms of export development - metallurgical, agro-industrial, transport and nuclear complexes, mechanical engineering, tourism, education and science. Based on the study, the article identifies the key directions of export development - strengthening the image of the region, international product promotion and attracting foreign capital.
Keywords: Regional Economy; Foreign Economic Activity; Export Activities; Export Support.